Pengembangan Prototipe Produk Wrapped Trouser Sebagai Media Pelatihan - Sasi, Sasi; Hidayati, Lutfiyah; Yuniati, Mita (PT. Riset Press International, 2025)
The purpose of this study is to find out (1) the process of making wrapped trouser product prototypes as a training medium (2) the finished results of making wrapped trouser product prototypes as training media. This research uses Research and Development (R&D) development research with PPE (Planning, Production, and Evaluation) development model. The method of collecting data from the process of prototyping wrapped trouser products as a training medium uses observation, while for the finished results of prototyping wrapped trouser products as a training medium using questionnaires from fashion experts. The results of this study show (1) the process of prototyping wrapped trouser products as a training medium, namely researching, making patterns, cutting toal materials, sewing toal, cutting main materials, sewing main materials (2) the results of prototyping wrapped trouser products as training media, which is used for archives for industrial sites, and becoming a prototype for formal or non-formal training.